Linked PNPLA3 polymorphisms confer susceptibility to nonalcoholic steatohepatitis and decreased viral load in chronic hepatitis B - Pan, Qin (World J Gastroenterol, 2015)
AIM: To investigate the association of PNPLA3 polymorphisms with concurrent chronic hepatitis B (CHB) and nonalcoholic fatty liver disease (NAFLD). METHODS: A cohort of Han patients with biopsy-proven CHB, with or without NAFLD (CHB group, n = 51; CHB + NAFLD group, n = 57), and normal controls (normal group, n = 47) were recruited from Northern (Tianjin), Central (Shanghai), and Southern (Zhangzhou) China. Their PNPLA3 polymorphisms were genotyped by gene sequencing. The association between PNPLA3 polymorphisms and susceptibility to NAFLD, and clinical characteristics of NAFLD were evaluated on the basis of physical indices, liver function tests, glycolipid metabolism, and histopathologic scoring. The association of PNPLA3 polymorphisms and hepatitis B virus (HBV) load was determined by the serum level of HBV DNA. RESULTS: After adjusting for age, sex, and body mass index, we found that four linked single nucleotide polymorphisms (SNPs) of PNPLA3, including the rs738409 G allele (CHB + NAFLD group vs CHB group: odds ratio [OR] = 2.77, 95% confidence interval [CI]: 1.18-6.54; P = 0.02), rs3747206 T allele (CHB + NAFLD group vs CHB group: OR = 2.77, 95%CI: 1.18-6.54; P = 0.02), rs4823173 A allele (CHB + NAFLD group vs CHB group: OR = 2.73, 95%CI: 1.16-6.44; P = 0.02), and rs2072906 G allele (CHB + NAFLD group vs CHB group: OR = 3.05, 95%CI: 1.28-7.26; P = 0.01), conferred high risk to NAFLD in CHB patients. In patients with both CHB and NAFLD, these genotypes of PNPLA3 polymorphisms were associated with increased susceptibility to nonalcoholic steatohepatitis (NASH) (NAFLD activity score ≥ 3; P = 0.01-0.03) and liver fibrosis (> 1 Metavir grading; P = 0.01-0.04). As compared to those with C/C and C/G at rs738409, C/C and C/T at rs3747206, G/G and G/A at rs4823173, and A/A and A/G at rs2072906, patients in the CHB + NAFLD group with G/G at rs738409, T/T at rs3747206, A/A at rs4823173, and G/G at rs2072906 showed significantly lower serum levels of HBV DNA (P < 0.01-0.05). CONCLUSION: Four linked SNPs of PNPLA3 (rs738409, rs3747206, rs4823173, and rs2072906) are correlated with susceptibility to NAFLD, NASH, liver fibrosis, and HBV dynamics in CHB patients.